2009
DOI: 10.5539/ijbm.v4n2p158
|View full text |Cite
|
Sign up to set email alerts
|

HR Roles Effectiveness and HR Contributions Effectiveness: Comparing Evidence from HR and Line Managers

Abstract: As the importance of human resource increases to the business, so does also the need to ensure its effective management. This study compared HR and line managers' evaluation of the effectiveness of the HR department in terms of its roles and contributions to the firm using a multi-perspective view of effectiveness. Survey responses from 108 HR and 140 line managers from 108 large manufacturing and service firms in Malaysia showed significant differences in the ratings by HR and line managers. HR managers, quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…More importantly, Wright et al (2001) found that line managers and HR executives displayed considerable agreement when rating HR's effectiveness across service categories (r=.89). Similar patterns are evident in Yusoff et al (2009). None of this suggests there is an appreciable risk the ratings we obtained were not fundamentally reflective of the underlying settings.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…More importantly, Wright et al (2001) found that line managers and HR executives displayed considerable agreement when rating HR's effectiveness across service categories (r=.89). Similar patterns are evident in Yusoff et al (2009). None of this suggests there is an appreciable risk the ratings we obtained were not fundamentally reflective of the underlying settings.…”
Section: Methodssupporting
confidence: 66%
“…Kahnweiler (2006) added that HR often is stymied by limited power and negative workforce perceptions. The pervasiveness of this dynamic is corroborated in surveys, where line managers are consistently less likely than HR respondents to believe that HR makes, or is capable of making, a strategic contribution to the firm (e.g., Clements, 2011;Payne, 2010;Woods, 2012;Wright, McMahan, Snell, & Gerhart, 2001;Yusoff, Abdullah, & Ramayah, 2009). Clements (2011) further observed an increasing negativity among line respondents regarding HR's perceived ability to be proactive, influential, and customer-focused in its dealings with the rest of the business.…”
Section: Introductionmentioning
confidence: 94%
“…In summary, theorists have emphasized the need for HRM to focus upon organizational change interventions from a strategic perspective, that is, a perspective which seeks to align the management of people within organizations with the successful implementation of business strategies (Schuler and Tarique, 2007). Yet, the same body of literature also highlights that managing strategic change in the Asia‐Pacific region is particularly problematic given both the transitional and heterogeneous features of the region and the emerging evidence of the lack of business‐related competencies among some HR professionals in countries such as Malaysia (Long and Ismail, 2008; Yusoff et al , 2009). To date, HRM literature on strategic change has reflected research in many situations in Western contexts and more developed countries in the Asia‐Pacific region such as Japan, Singapore, and Korea.…”
Section: Hrm and Organizational Change: The Search For A Strategic Focusmentioning
confidence: 99%
“…Unfortunately, several studies recently indicated that many HR professionals in Asia are still lagging behind as a change agent compared to the western counterpart [3 [7] 1999). Furthermore, a study by Yusoff, et al [8] claims that HR role effectiveness as change agent is among the lowest in the manufacturing and servicing sector of Malaysia. Therefore, this study will address the above issue by looking into critical competencies required of HR professionals in order for them to function effectively as change agents.…”
Section: Introductionmentioning
confidence: 99%